Mekanisme Pengungkapan Fraud: Studi Kasus Hambalang Dan Skandal PT Garuda Indonesia - Putri Nurdiani; Prastianti, Prastianti; Muhamad Andriansyah; Sabrina Pransiska; Nia Maryani; Febri Yunita Chaurisma; Siti Nurandin; Windi Patikasari; Muhamad Galang Fajar Anugrah Putra; Wulandari, Wulandari (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This study analyzes the fraud disclosure mechanism in the Hambalang project corruption case and the PT Garuda Indonesia financial report scandal. Using a case study approach and secondary data, the research identifies the disclosure process, barriers, and recommendations to strengthen fraud prevention. The results show that investigative audits, supervisory institutions (BPK, KPK, OJK, IDX), as well as the media and the public play an important role in fraud disclosure. However, political pressure, complex inter-agency coordination, and weak internal controls are the main obstacles. To overcome this, the study recommends improving regulations, utilizing technology such as AI, governance transparency, strict sanctions, strengthening whistleblowing systems, and training for auditors. With these measures, fraud detection systems can be strengthened, financial losses minimized, and public trust in government institutions and companies increased.